Concomitant endometriosis in malignant and borderline ovarian tumours*. (17th November 2018) - Oral, Engin; Aydin, Ovgu; Kumbak, Banu Aygun; İlvan, Sennur and Yilmaz, Handan and Tustas, Esra and Bese, Tugan and Demirkiran, Fuat and Arvas, Macit
Abstract: The aim of the study was to reveal the prevalence of concomitant endometriosis in malignant and borderline ovarian tumours. A retrospective analysis was performed of 530 patients with malignant ovarian tumours and 131 with borderline ovarian tumours, who underwent surgery in our hospital between 1995 and 2011. Forty-eight (7.3%) of 661 patients with malignant and borderline ovarian tumours were associated with endometriosis. Of the 48 endometriosis cases, 73% of those were atypical. Infertility was noted in 38% of patients with endometriosis-associated ovarian tumours. The most frequently endometriosis-associated subtypes were endometrioid (33%) and clear cell (18%) histologies. Of endometriosis-associated endometrioid and clear cell ovarian tumours, 70% were early stage and 60% were premenopausal. The prevalence of concomitant endometriosis in borderline tumours (12%) was found to be significantly higher than that found in the malignant ones (6%; p = .02). Of 32 endometriosis-associated malignant ovarian tumours, 69% were FIGO stages I and II. In conclusion, ovarian endometriosis is seen with both malignant and borderline ovarian tumours, the association being significant with borderline tumours. Fortunately, the endometriosis-associated malignant ovarian tumours are mostly early stage. Impact statement: What is already known on this subject? Epidemiologic data suggest that endometriosis has malignant potential. However, a subgroup of women with endometriosis at a high risk for ovarian cancer is yet to be clarified. Currently, endometriosis and ovarian cancer association does not seem to have a clinical implication. What do the results of this study add? The findings of this study revealed that nearly 75% of endometriosis-associated ovarian tumours were of atypical endometriosis. Half of endometriosis-associated ovarian tumour cases were of endometrioid/clear cell histology and 70% were early-stage. Endometriosis was significantly associated with borderline ovarian tumours and the endometriosis-associated malignant ovarian tumours were mostly early stage. What are the implications of these findings for clinical practice and/or further research? Additional studies need to be conducted to develop screening approaches for malignant transformation or an association in women with endometriosis. Till that time, a change of current clinical practices cannot be justified. However, counselling and treating women with endometriosis who are at high risk for cancer coexistence or conversion is encouraged.